Structural alterations of skeletal muscle in copd - Mathur, Sunita; Brooks, Dina; Carvalho, Celso R. (Frontiers in Physiology, 2014)
Background: Chronic obstructive pulmonary disease (COPD) is a respiratory disease associated with a systemic inflammatory response. Peripheral muscle dysfunction has been well characterized in individuals with COPD and results from a complex interaction between systemic and local factors. Objective: In this narrative review, we will describe muscle wasting in people with COPD, the associated structural changes, muscle regenerative capacity and possible mechanisms for muscle wasting. We will also discuss how structural changes relate to impaired muscle function and mobility in people with COPD. Key Observations: Approximately 30-40% of individuals with COPD experience muscle mass depletion. Furthermore, muscle atrophy is a predictor of physical function and mortality in this population. Associated structural changes include a decreased proportion and size of type-I fibers, reduced oxidative capacity and mitochondrial density mainly in the quadriceps. Observations related to impaired muscle regenerative capacity in individuals with COPD include a lower proportion of central nuclei in the presence or absence of muscle atrophy and decreased maximal telomere length, which has been correlated with reduced muscle cross-sectional area. Potential mechanisms for muscle wasting in COPD may include excessive production of reactive oxygen species, altered amino acid metabolism and lower expression of peroxisome proliferator-activated receptors-gamma-coactivator 1-alpha mRNA. Despite a moderate relationship between muscle atrophy and function, impairments in oxidative metabolism only seems weakly related to muscle function. Conclusion: This review article demonstrates the cellular modifications in the peripheral muscle of people with COPD and describes the evidence of its relationship to muscle function. Future research will focus on rehabilitation strategies to improve muscle wasting and maximize function.